Late Quaternary environmental changes in Misiones, subtropical NE Argentina, deduced from multi-proxy geochemical analyses in a palaeosol-sediment sequence - Zech, MIchael (2009)
A 4.5-m-long sediment core from a small basin in the Province of Misiones, NE Argentina, was analyzed in a multi-proxy geochemical approach (major and minor elemental composition, Corg, N, HI, OI, δ13Corg, n-alkanes and compound-specific δ13C analyses of biomarkers) in order to contribute to the reconstruction of the Late Quaternary environmental and climate history of subtropical South America. The results of the elemental analyses and radiocarbon dating indicate different sediment provenances for Unit A—the Holocene, Unit B—the Late Glacial and the Last Glacial Maximum (LGM), and Unit C—the ‘Inca Huasi’ wet phase (before ∼40 ka BP). A sedimentary hiatus after ∼40 ka BP is interpreted as a pronounced pre-LGM dry phase with landscape erosion/deflation. Multi-proxy geochemical characterization of the soil organic matter (SOM) shows that especially (i) the stable carbon isotopic composition (δ13C) of the grass-derived alkanes nC31 and nC33, (ii) the alkane ratio nC31/nC27 and (iii) lacustrine-derived short- and mid-chain alkanes are valuable proxies for the reconstruction of the palaeoenvironment. A transition from C3-tree-dominance to C4-grass-dominance is recorded at the end of the ‘Inca Huasi’ wet phase. In Unit B, the ratio nC31/nC27 documents forest expansion at the beginning of a Late Glacial wet phase. More positive δ13C values in Unit A reflect the increasing contribution of C4-grasses and/or CAM-plants to the SOM during the Holocene and a human impact on the formation of this unit may be possible. The results are in good agreement with other tropical/subtropical palaeoenvironmental records and highlight the importance and temporal variability of the palaeo-South American Summer Monsoon (SASM).